Zaposlovanje in pogodba o zaposlitvi javnih uslužbencev z vidika pogodbenosti uslužbenskih razmerij - Korpič-Horvat, Etelka (Delavci in delodajalci, 2020)
In her article, the author discusses the public competition, the selection procedure, the conclusion and the contents of the employment contract, which according to the ZJU (Public Servants Act) applies to officials from the point of view of contractual employment. In Slovenia, officials, too, conclude employment contracts, which can significantly contribute to greater convergence or unification of employment and service relations, which was set as the goal of the Public Administration Development Strategy for the period 2015-2020. It finds that, for the protection of a civil servant as a weaker party and for the protection of public interest, employment relationships are strictly bound by regulations and collective agreements, which severely restricts the executives in determining the rights and obligations of civil servants. Principals are becoming executors of norms, not managers of employees with the authority to organize successful operations in the public sector.
Keywords: civil servants; delavci; employment contract; javni interes; javni natečaj; javni sektor; official; pogodba o zaposlitvi; public competition; public interest; public sector; uradniki; workers